Pharmacoinformatics and drug discovery technologies : theories and applications - Tagelsir Mohamed Gasmelseid
Offers the latest the field has to offer to practitioners and academics alike, presented through theoretical frameworks, case studies, and future directions. This vital resource gathers an integrated pattern of high quality publications from around the world providing current, cutting-edge, and provocative scientific work in the three domains of pharmacoinformatics: decision making domains, knowledge utilization and representation environment, and the technological and infrastructural context